Methylation-Induced Silencing of ALDH2 Facilitates Lung Adenocarcinoma Bone Metastasis by Activating the MAPK Pathway - Yang, Mengdi; Wang, AiTing; Li, Changcan; Sun, Jing; Yi, Gang; Cheng, Hao; Liu, Xueni; Wang, Zhiyu; Zhou, Yiyi; Yao, Guangyu; Wang, Shuai; Liang, Rui; et al. (Frontiers in Oncology, 2020)
Bone metastasis (BM) dramatically reduces the quality of life and life expectancy in lung adenocarcinoma (LUAD) patients. There is an urgent need to identify potential biomarkers for application in the treatment of this deadly disease. We compared patient BM, LUAD, and para-LUAD tissues using proteomic analysis and identified Aldehyde Dehydrogenase 2 (ALDH2), which can detoxify acetaldehyde to acetic acid, as one of the key regulators in lung tumor metastasis. Both the mRNA and protein levels of ALDH2 were significantly lower in tumor tissues than in normal tissues and were lowest in BM tissues with increased migratory capacity. Also, ALDH2 was upregulated following treatment with 5-azacytidine, a DNA methyltransferase inhibitor, in H1299, H460, and HCC827 cells. Further, we identified a potential methylated CpG island 3, with the longest methylated CpG island area in ALDH2, and performed bisulfite genomic sequencing of these sites. An average of 78.18% of the sites may be methylated in CpG island 3. Knockdown of DNA (cytosine-5)-methyltransferase 3A (DNMT3A) and methylated CpG binding protein 4 (MBD4) upregulated ALDH2 expression. ALDH2 functions as a MAPK upstream to inhibit cell proliferation and migration, promote cell apoptosis, and alter the epithelial-mesenchymal transition (EMT) by elevating E-Cadherin and attenuating Vimentin. Cell proliferation and migration were inhibited after the addition of the JNK inhibitor SP600125. In the multivariate analysis, M stage (p= 0.003), ALDH2 (p= 0.008) and p-JNK (p=0.027) expression were independent prognostic factors for overall survival in patients with BM. In vivo experiments also showed that ALDH2 expression could suppress tumor formation. In summary, we found that ALDH2 expression is a prognostic factor for BM in LUAD and that DNMT3A and MBD4 repression of ALDH2 via a MAPK dependent pathway altering the EMT process, indicating that these proteins could act as potential biomarkers or therapeutic targets for LUAD metastasis.